Selective Spectrophotometric and Spectrofluorometric Methods for the Determination of Amantadine Hydrochloride in Capsules and Plasma via Derivatization with 1,2-Naphthoquinone-4-sulphonate - Ashraf M. Mahmoud; Nasr Y. Khalil; Ibrahim A. Darwish; Tarek Aboul-Fadl (International Journal of Analytical Chemistry)
New selective and sensitive spectrophotometric and spectrofluorometric methods have been developed and validated for the determination of amantadine hydrochloride (AMD) in capsules and plasma. The methods were based on the condensation of AMD with 1,2-naphthoquinone-4-sulphonate (NQS) in an alkaline medium to form an orange-colored product. The spectrophotometric method involved the measurement of the colored product at 460  nm. The spectrofluorometric method involved the reduction of the product with potassium borohydride, and the subsequent measurement of the formed fluorescent reduced AMD-NQS product at 382  nm after excitation at 293  nm. The variables that affected the reaction were carefully studied and optimized. Under the optimum conditions, linear relationships with good correlation coefficients (0.9972–0.9974) and low LOD (1.39 and 0.013 𝜇g mL−1) were obtained in the ranges of 5–80 and 0.05–10 𝜇g mL−1 for the spectrophotometric and spectrofluorometric methods, respectively. The precisions of the methods were satisfactory; RSD ≤2.04%. Both methods were successfully applied to the determination of AMD in capsules. As its higher sensitivity, the spectrofluorometric method was applied to the determination of AMD in plasma; the recovery was 96.3–101.2±0.57–4.2%. The results obtained by the proposed methods were comparable with those obtained by the official method